Computation of the 3D kinematics in a global frame over a 40 m-long pathway using a rolling motion analysis system - Begon, M.; Colloud, F.; Fohanno, V.; Bahuaud, P.; Monnet, T. (Journal of Biomechanics, 2009)
A rolling motion analysis system has been purpose-built to acquire an accurate three-dimensional kinematics of human motion with large displacement. Using this device, the kinematics is collected in a local frame associated with the rolling motion analysis system. The purpose of this paper is to express the local kinematics of a subject walking on a 40 m-long pathway in a global system of co-ordinates. One participant performed five trials of walking while he was followed by a rolling eight camera optoelectronic motion analysis system. The kinematics of the trials were reconstructed in the global frame using two different algorithms and 82 markers placed on the floor organized in two parallel and horizontal lines. The maximal error ranged from 0.033 to 0.187 m (<0.5% of the volume diagonal). As a result, this device is accurate enough for acquiring the kinematics of cyclic activities with large displacements in ecological environment.